Antoine Equation Coefficients for Novichok Agents (A230, A232, and A234) via Molecular Dynamics Simulations - Michail Chalaris; Antonios Koufou (Physchem, 2023)
The flexible models of Novichok agents (A230, A232, and A234) from previous molecular dynamics simulations (MDSs) have been employed to create a parameter set for the Antoine equation of each of the three liquids. Furthermore, for the needs of this paper, new models of Novichok agents were created and studied via MDS due to the fact that the exact molecular structure of these compounds has been a matter of discussion in the last few years; however, recently, the literature favors a particular set of structures. Therefore, to cover our study holistically, both of the proposed molecular formulas were employed in the simulations and discussion. A range of ambient conditions was selected, and the data from the molecular dynamics simulations were employed to give the best possible fit in the selected vapor pressure range. When looking at the results for the two structures of A230, A232, and A234, we can see that, despite their differences, the A and B coefficients have the same magnitude in both cases (structures proposed by Ellison and Hoenig and structures proposed by Mirzayanov). Moving from the Ellison and Hoenig to Mirzayanov structures for substances A230 and A234 revealed a decrease (slight to major) in factors A and B of the Antoine equation. However, in the case of A232, where the Mirzayanov structure produces higher coefficients, this does not hold true. Overall, the Antoine equation of the studied agents will be an essential tool for understanding the behavior of these substances under different conditions.